Dropwise condensation reduces selectivity of sky-facing radiative cooling surfaces. (1st December 2022) - Simsek, Eylul; Mandal, Jyotirmoy; Raman, Aaswath P.; Pilon, Laurent
Highlights: First spectral characterization for droplet-covered selective emitters. The droplet contact angle varied from 39 to 62o and surface area coverage up to 50%. The droplets increase and broad the spectral emittance of the selective emitter. The droplets reduce selectivity of radiative cooling surfaces. Temperature of the radiative cooling surface increased when covered with droplets. Abstract: Dew formation occurs frequently on radiative cooling surfaces used for cooling of buildings and for harvesting atmospheric water as a result of dropwise condensation. The presence of these droplets can in turn alter the infrared emittance and performance of radiative cooling surfaces, in particular, selective emitters. This study experimentally investigates the impact of dropwise condensation on both the emittance and spectral selectivity of radiative cooling surfaces. Here, selective emitters supporting a large number of polydisperse acrylic droplets, as water droplet simulant, with contact angle ranging between 39° and 62° and surface area coverage between 20% and 52% were prepared and characterized. Spectral characterization revealed that the spectral emittance of the radiative cooling surfaces increased and broadened significantly in the presence of droplets. This was attributed to the absorption by the droplets. The emittance inside the long-wavelength infrared (LWIR) atmospheric transparency window increased slightly while the emittance outside increased significantly with increasing droplet surface area coverage and contact angle. This loss in spectral selectivity resulted in heat gain from radiation exchanges outside the LWIR, such that a given radiative cooling surface attained a higher temperature when covered with droplets. Dew formation may thus present important limitations on the performance achievable by selective emitters in radiative cooling applications.